Peran Negara dalam Pengelolaan Keuangan Publik di Indonesia: Tinjauan Kitab Al-Amwal Karya Abu Ubaid - Yahya Ismail, Raihan; Fadilah, Dimas; Munajat, Ma’mur; Achmad Sadat, Fahad (Green Publisher Indonesia, 2025)
The purpose of this research is to analyze the role of the state in financial management in Indonesia by referring to the book Al-Amwal by Abu Ubaid Al-Qassim bin Salam. This book is the most important reference work in Islamic economics, containing philosophical and practical views on financial principles based on justice, public welfare, and transparency. The main principles highlighted by Abu Ubaid include justice in the distribution of wealth, and the control of public sources of income such as zakat, kharaj, jizyah, as well as the role of Baitul Maal as the main national financial institution. This study also discusses the relevance of the principles of the book of Al-Amwal to the public financial management system in Indonesia. This study uses a qualitative approach with a library research method. Literature review or library research, which is a research method carried out through the collection, analysis, and synthesis of information from various relevant literature sources. The results of the analysis show that values such as fairness, efficiency, fiscal balance, and public welfare are in line with Indonesia's fiscal policies, such as redistributive programs through the General Allocation Fund (DAU) and progressive tax management. Despite challenges such as corruption and economic inequality, Abu Ubaid's principles provide philosophical guidance for strengthening the transparency, accountability, and sustainability of the public financial system.